Gallium oxide mixed-phase thin film, ultraviolet detector and preparation method of gallium oxide mixed-phase thin film

By introducing 5~15at% zinc doping into the gallium oxide-based ultraviolet detector, a single-climb phase and hexagonal phase hybrid structure is formed, which solves the problems of slow response speed and insufficient comprehensive performance, and achieves more efficient photoelectric detection performance and stability sex.

CN119300539APending Publication Date: 2025-01-10CHANGCHUN INST OF OPTICS FINE MECHANICS & PHYSICS CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411495830.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing gallium oxide-based ultraviolet detectors face the problems of slow response speed and insufficient comprehensive performance, especially due to the influence of lattice distortion and oxygen vacancies caused by impurity incorporation, which affects the conductivity and photoelectric detection performance of the material.

Method used

Using 5~15at% zinc-doped gallium oxide mixed phase film, including two crystal phases of β-Ga2O3 in monoclinic crystal system and ε-Ga2O3 in hexagonal crystal system, the film is grown under specific conditions through MOCVD technology to form a mixed phase structure to improve the optical and electrical properties of the material.

Benefits of technology

By destroying the continuous crystal lattice, reducing oxygen vacancies concentration, enhancing carrier lifetime, improving photoresponsiveness and device robustness, and maintaining superior detection performance in high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300539A_ABST
    Figure CN119300539A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductor detectors, in particular to a gallium oxide mixed-phase thin film, an ultraviolet detector and a preparation method of the gallium oxide mixed-phase thin film. The gallium oxide mixed-phase thin film is doped with 5-15 at% of zinc, and the crystal phases comprise two crystal phases, namely beta-Ga2O3 of a monoclinic system and epsilon-Ga2O3 of a hexagonal system; the preparation method comprises the following steps: cleaning a substrate; the substrate tray is heated to 500 DEG C to 950 DEG C, and the internal pressure is kept at 1000 Pa to 2000 Pa; introducing high-purity nitrogen; a zinc organic source and a gallium organic source are introduced in an equal proportion every 5-30 min, and the condition is kept for 20-50 min after the final gas carrying capacity is achieved; slowly introducing high-purity oxygen until the flow rate of the oxygen reaches 500-1000sccm and is constant, and slowly growing zinc-doped Ga2O3; and growing for 80-150 minutes to obtain the gallium oxide mixed phase thin film. The invention has the advantages of high stability, good robustness and enhanced light response in the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor detectors, and in particular to a gallium oxide mixed phase film, an ultraviolet detector and a preparation method thereof. Background Art

[0002] Ultraviolet detection is a new technology that uses photoelectric detectors to convert the light signal of ultraviolet light irradiating the device into an electrical signal through external photoelectric effect or internal photoelectric effect. It has broad application prospects in military and civilian fields such as ultraviolet early warning, radiation calibration, communication technology, ultraviolet imaging, food and drug testing, etc.

[0003] There are three main types of UV detection devices with relatively mature technology: vacuum photomultiplier tubes, which require a high-voltage environment to work and are greatly affected by high temperature and electromagnetic radiation; silicon-based photodiodes, narrow-bandgap detectors, which respond to both UV and visible light and need to work with multiple filters; detectors based on wide-bandgap materials, including nitrides such as diamond, silicon carbide (SiC), gallium nitride (GaN), and gallium oxide (Ga2O3), zinc oxide (ZnO) oxide. Among them, detectors based on oxide materials have gradually become a research hotspot in the field of UV detection due to their excellent photoelectric detection performance, spectral response peak corresponding to the deep ultraviolet light region, high stability, and sensitive response.

[0004] There are many kinds of wide bandgap oxide materials reported so far, among which β -Ga2O3 has a bandgap of approximately 4.8eV-4.9eV, and the corresponding wavelength is just in the solar-blind ultraviolet band. The material has good stability, strong radiation resistance, and a high breakdown electric field. These special advantages give gallium oxide materials a broad development prospect in the field of ultraviolet detection. Pure β- Ga2O3 is an insulating material, but it is limited by the current growth technology. Whether it is magnetron sputtering, molecular beam epitaxy or metal organic chemical vapor deposition, there will always be inadvertent impurities added during epitaxial growth, and the film after epitaxial growth exhibits N-type conductivity. The benefit of doping is that introducing a small amount of impurity atoms or ions into Ga2O3 may cause changes in the bond lengths and angles between atoms at the lattice points, forming lattice distortion, and on the other hand, the doping elements will occupy vacancy defects in the lattice, affecting the lattice integrity. Both of these situations may affect the oxygen vacancy concentration in the material. Regarding doping, there have been quite a few research reports at home and abroad. Earlier, silicon, germanium and other elements were doped to act as donor impurities to provide free carriers, thereby showing good conductivity and high carrier mobility. Later, researchers used nitrogen atoms and hydrogen atoms to passivate the properties of the surface and internal lattice defects of the material. The purpose was to passivate the acceptor state existing in the growth of gallium oxide film, thereby enhancing the conductivity of the film. When doping with these two elements, it should be noted that the stability of the two atoms on the microscopic lattice points of gallium oxide is not high. Next, the elements originally used to study the realization of P-type conductivity, such as magnesium, zinc, and aluminum, have a limited hole concentration that can be achieved after doping at room temperature because of the deep acceptor energy level inside gallium oxide, and the success rate is very low. It is worth noting that the researchers also found that doping aluminum in gallium oxide improves the thermal stability of the film and the device. Zinc and magnesium can increase the concentration of free electrons inside gallium oxide within a certain doping concentration range. Most importantly, the oxygen vacancy defects originally existing in the film after doping are compensated, and the performance of the device in all aspects will be improved to a certain extent.

[0005] The ionic radius of zinc is very close to that of gallium, so it is easier for zinc to move from the interstitial position of the gallium oxide lattice to the position of gallium in the gallium oxide lattice during doping, thus achieving more efficient doping. β -Doping an appropriate amount of Zn into the Ga2O3 film can change the oxygen vacancy concentration in the film, reduce the dark current of the film, and reduce the persistent photoconductivity effect; after doping with Zn, among the three characteristic excitation bands observed, the ultraviolet emission and blue light emission are enhanced, the average absorption of the intrinsic film is reduced, and the average absorption of the zinc-doped film is significantly increased. With the increase of the doping level, the lattice gradually expands and the band gap gradually increases. Under the irradiation of ultraviolet light, the responsiveness of the photodetector increases and the relaxation time decreases. The introduction of Zn components in the gallium oxide material increases. Through this multi-component doping, the oxygen coordination and long-range structural anisotropy of the material that originally belonged to the monoclinic phase, as well as the electronic configuration of the cation and the hybridization state of the adjacent oxygen atoms will change. Currently, researchers are mainly focusing on β-Ga2O3 single crystal phase is doped with zinc elements of different components in order to obtain a UV detector with better performance. Some researchers have reported that if a mixed phase is formed, the doping result will be counterproductive and reduce the performance of the device. However, for a mixed phase formed by multiple different crystal phases in a material or crystal phases of different materials, the degree of mixed phase is well controlled, that is, which crystal phase is dominant in the film. This combined phase structure can obtain various customized properties that cannot be achieved by single-phase materials. The interaction between different phases in the mixed phase material can produce a synergistic effect and improve the optical and electrical properties of the device. At present, Ga2O3-based UV detectors still face problems such as slow response speed and insufficient comprehensive performance. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a gallium oxide mixed phase film, an ultraviolet detector and a preparation method thereof.

[0007] The first object of the present invention is to provide a gallium oxide mixed phase film, wherein the gallium oxide mixed phase film is doped with 5-15at% zinc, and the crystal phases include two crystal phases: monoclinic β-Ga2O3 and hexagonal ε-Ga2O3.

[0008] Preferably, it is prepared by the following method: S1. Clean the substrate and place it in the growth chamber of the MOCVD equipment; heat the substrate tray to 500~950℃ and keep the internal pressure at 1000~2000Pa; S2. Pass high-purity nitrogen for 30 to 50 minutes to exhaust the residual oxygen; set the source temperature of the zinc organic source and gallium organic source precursors, pass the zinc organic source and gallium organic source in equal proportion every 5 to 30 minutes, and maintain for 20 to 50 minutes after reaching the final carrier gas volume of the zinc organic source and gallium organic source; S3. Slowly introduce high-purity oxygen, with the oxygen flow rate increasing from 0 sccm by 50-200 sccm every 10-30 minutes until the oxygen flow rate reaches 500-1000 sccm and then becomes constant, and slowly grow zinc-doped Ga2O3 on the substrate; S4. Grow for 80 to 150 minutes under the oxygen flow state of step S3 to obtain a gallium oxide mixed phase film.

[0009] Preferably, in step S1, the substrate tray is heated to 750-950°C, and the internal pressure is maintained at 1000Pa.

[0010] Preferably, in step S2, the source temperatures of the zinc organic source and gallium organic source precursors are -10~-5°C and 8~12°C respectively; the final carrier gas volumes of the zinc organic source and gallium organic source are 0.5~1.5sccm and 6~15sccm respectively, the flow rate of the zinc organic source changes from 0sccm to 0.1~0.3sccm, and the flow rate of the gallium organic source changes from 0sccm to 1.5~3.5sccm.

[0011] Preferably, in step S2, the source temperatures of the zinc organic source and gallium organic source precursors are -8°C and 10°C, respectively; and the final carrier gas volumes of the zinc organic source and gallium organic source are 1.2 sccm and 7.2 sccm, respectively.

[0012] Preferably, in step S3, the oxygen flow rate is increased linearly by 200 sccm every 10 minutes until the oxygen flow rate reaches 800 sccm and then remains constant.

[0013] Preferably, the thickness of the gallium oxide mixed phase film is 200-400 nm.

[0014] The second object of the present invention is to provide a gallium oxide mixed phase ultraviolet detector, which comprises, from bottom to top, a substrate, the gallium oxide mixed phase film and interdigital electrodes; The thickness of the interdigital electrode is 50-100 nm, and the effective illumination area is preferably in the range of 0.25-1 mm 2 .

[0015] Preferably, the length of the interdigital electrodes is 400-600 um, and the width between the fingers is 10 um; the material of the interdigital electrodes is gold or aluminum.

[0016] Preferably, the method is as follows: epitaxially growing a gallium oxide mixed phase film on a substrate; and depositing the interdigital electrodes on the gallium oxide mixed phase film using a photolithography technique.

[0017] Compared with the prior art, the present invention can achieve the following beneficial effects: The present invention provides a gallium oxide mixed phase film and a preparation method thereof, and designs a photodetector with better performance on this basis; the method obtains a monoclinic phase and a hexagonal phase mixed structure by doping while maintaining the gallium oxide material as the main body, and makes the original pure gallium oxide-based ultraviolet detector, which is criticized for its continuous photoconductivity effect, weaker by destroying the continuous lattice and reducing the concentration of oxygen vacancies in the material. At the same time, the discontinuity of the interface also hinders the transit process of minority carrier holes, greatly increases the carrier life, and enhances the light response in the device, which proposes a new research idea for the current research on gallium oxide-based photodetectors. The method of the present invention has high stability and good robustness, and can maintain excellent detection ability even under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a SEM image of a gallium oxide mixed phase thin film provided according to an embodiment of the present invention.

[0019] Figure 2 is an AFM image of a gallium oxide mixed phase film provided according to an embodiment of the present invention.

[0020] Figure 3 This is an XRD diagram of controlling the substrate temperature within a preferred temperature range (500-900° C.) provided in an embodiment of the present invention.

[0021] Figure 4 This is an XRD diagram of regulating the precursor oxygen flow rate within a preferred range (400-800 sccm) provided in an embodiment of the present invention.

[0022] Figure 5 1 is an XRD spectrum of a gallium oxide mixed phase film provided according to an embodiment of the present invention; the figure reflects the two phase structures of monoclinic phase and hexagonal phase existing in the film.

[0023] Figure 6 is an image of the atomic ratio of zinc and gallium in a gallium oxide mixed phase thin film provided according to an embodiment of the present invention.

[0024] Figure 7 Schematic diagram of the structure of a gallium oxide mixed-phase ultraviolet detector provided according to an embodiment of the present invention.

[0025] Figure 8 It is a current-voltage image of the gallium oxide mixed phase ultraviolet detector provided according to an embodiment of the present invention under light and in a dark environment.

[0026] Fig. 9 This is a photocurrent-time image of a gallium oxide mixed-phase ultraviolet detector under multi-cycle conditions provided by an embodiment of the present invention.

[0027] Reference numerals: 1. Substrate; 2. Gallium oxide mixed phase thin film; 3. Interdigitated electrodes. DETAILED DESCRIPTION

[0028] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. In the following description, the same modules are represented by the same reference numerals. In the case of the same reference numerals, their names and functions are also the same. Therefore, the detailed description thereof will not be repeated.

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not constitute a limitation of the present invention.

[0030] The present invention provides a gallium oxide mixed phase film, wherein the gallium oxide mixed phase film is zinc-doped, and the crystal phases include two crystal phases of monoclinic β-Ga2O3 and hexagonal ε-Ga2O3; the preparation steps are as follows: S1. Clean the substrate and place it in the growth chamber of the metal organic chemical vapor deposition (MOCVD) equipment; heat the substrate tray to 500~950℃ (growth temperature) and keep the internal pressure at 1000~2000Pa; Specifically, the substrate is oxygen-polar C-plane sapphire; the preferred range of the growth temperature is 750° C. to 950° C.; In a specific embodiment, the substrate tray is heated to 800° C. and the internal pressure is maintained at 1000 Pa.

[0031] S2. Pass high-purity nitrogen for 30 to 50 minutes to expel residual oxygen; set the source temperature of zinc organic source and gallium organic source precursors, pass zinc organic source and gallium organic source in equal proportion every 5 to 30 minutes, and maintain for 20 to 50 minutes after reaching the final carrier gas volume of zinc organic source and gallium organic source; The source temperatures of zinc organic source and gallium organic source precursors are -10~-5℃ and 8~12℃ respectively; the final carrier gas volumes of zinc organic source and gallium organic source are 1~1.5sccm and 7~7.5sccm respectively, the flow rate of zinc organic source changes from 0sccm to 0.1~0.3sccm, and the flow rate of gallium organic source changes from 0sccm to 1.5~3.5sccm; In a specific embodiment, high-purity nitrogen is introduced into the reaction chamber for 30 minutes in advance, and the source temperatures of the zinc organic source and gallium organic source precursors are set to -8°C and 10°C, respectively; the final carrier gas volumes of the zinc organic source and the gallium organic source are 1.2sccm and 7.2sccm, respectively, and the flow rate of the zinc organic source changes by 0.3sccm from 0sccm, and the flow rate of the gallium organic source changes by 1.8sccm from 0sccm. They are introduced into the reaction chamber in equal proportions every 10 minutes until the predetermined maximum organic source flow rate is reached, and this state is maintained for 20 minutes.

[0032] S3. Slowly introduce high-purity oxygen, with the oxygen flow rate increasing from 0 sccm by 50-200 sccm every 10-30 minutes until the oxygen flow rate reaches 500-1000 sccm and then becomes constant, and slowly grow zinc-doped Ga2O3 on the substrate; In a specific embodiment, the oxygen flow rate starts from 0 sccm and increases linearly by 200 sccm every 10 minutes until the oxygen flow rate reaches 800 sccm and then remains constant.

[0033] S4. Then grow for 80 to 150 min under the oxygen flow state in step S3 to obtain a gallium oxide mixed phase film; preferably, the growth time is 120 min; The preferred range of the thickness of the gallium oxide mixed phase film is 200-400 nm; The crystal phase of the gallium oxide mixed phase film is a mixed phase of monoclinic β-Ga2O3 and hexagonal ε-Ga2O3. A zinc-doped gallium oxide mixed phase film with a preferred range of 5 to 15 at% is grown by regulating the organic source growth flow rate.

[0034] The present invention also provides a gallium oxide mixed phase ultraviolet detector, which comprises, from bottom to top, a substrate, a gallium oxide mixed phase film prepared by the above method, and interdigital electrodes; The thickness of the interdigital electrode is preferably in the range of 50-100 nm, the length of the interdigital electrode is preferably in the range of 400-600 μm, and the width between the fingers is 10 μm; the material of the interdigital electrode is gold or aluminum, and the effective illumination area is preferably in the range of 0.25-1 mm 2 ; The interdigitated electrodes are deposited by photolithography technology; In a specific embodiment, the thickness of the interdigital electrode is about 80nm, the length of the interdigital electrode is 500um, and the effective illumination area is 0.25mm 2 about.

[0035] Example 1 This embodiment provides a method for preparing a gallium oxide mixed phase thin film, and the specific steps are as follows: S1. Clean the oxygen-polar C-plane sapphire substrate and place it in a MOCVD growth chamber; S2. Pass high-purity nitrogen for 30 minutes to expel residual oxygen; set the source temperature of zinc organic source and gallium organic source precursors to -8°C and 10°C, respectively, the flow rate of zinc organic source changes from 0 sccm to 0.3 sccm, the flow rate of gallium organic source changes from 0 sccm to 1.8 sccm, the final carrier gas volume of zinc organic source and gallium organic source is 1.2 sccm and 7.2 sccm, respectively, and maintain this state for 20 minutes; S3. The reaction chamber is now filled with two organic source molecules, and some of the organic source molecules are cracked near the sapphire substrate. At this time, high-purity oxygen is slowly introduced, and the two organic molecules of gallium and zinc can react directly on the substrate surface. The oxygen flow rate starts from 0 sccm and increases linearly. The oxygen flow rate increases by 200 sccm every 10 minutes until it reaches 800 sccm. During these 40 minutes, Ga2O3 grows slowly, which can well eliminate the influence of lattice mismatch. S4. Then, the mixture is grown for 120 min at an oxygen flow rate of 800 sccm to obtain a gallium oxide mixed phase film.

[0036] Figure 1 Shown is a hybrid structured gallium oxide surface ( Figure 1 Middle left) and cross section ( Figure 1 (middle right picture) It can be seen that the surface grains of the film are evenly distributed and the thickness of the film is about 200nm.

[0037] Figure 2 Depicting the 3D image of the film's surface undulations is a demonstration of the high quality of the film's epitaxial growth.

[0038] By changing the temperature (500~900℃), the effect on the phase separation of the film was observed. Figure 3 Finally, the conditions with the best crystal quality within the preferred range are selected for implementation.

[0039] In the early stage, the precursor oxygen flow rate (400~800sccm) is adjusted to achieve the growth of high-quality films, such as Figure 4 shown.

[0040] Through XRD patterns, such as Figure 5 As shown, it can be clearly seen that there are two peaks of gallium oxide at 2θ = 20°, 39°, and 59°. By comparing with the standard card of gallium oxide, it can be obtained that the two crystal phases are monoclinic β-Ga2O3 and hexagonal ε-Ga2O3.

[0041] Figure 6 It represents the proportion of each element in the film. We only focus on the atomic ratio of zinc and gallium. The content of Zn in the grown mixed phase film material is 6.5at%.

[0042] Example 2 like Figure 7 As shown, this embodiment provides a gallium oxide mixed phase ultraviolet detector, which includes, from bottom to top, a substrate 1, a gallium oxide mixed phase film 2, and an interdigital electrode 3; Substrate 1 is a C-plane sapphire substrate; The gallium oxide mixed phase film 2 is a 6.5at% zinc-doped gallium oxide-based mixed phase film including two crystal phases of monoclinic β-Ga2O3 and hexagonal ε-Ga2O3; The thickness of the interdigital electrode 3 is about 80nm, and the effective illumination area is preferably in the range of 0.25mm 2 ; The length of the interdigital electrodes 3 is 500 um, and the width between the fingers is 10 um; the material of the interdigital electrodes 3 is gold or aluminum.

[0043] The preparation method comprises: Epitaxially growing a gallium oxide mixed phase thin film 2 on a substrate 1 according to the method of Example 1 (steps S1 to S4); The interdigital electrodes 3 are deposited on the gallium oxide mixed phase film 2 by using photolithography technology.

[0044] The photoelectric performance of the UV detector device prepared in this embodiment was tested. For the IV characteristics of the device, 254 nm UV light with an optical power density of 0.6 mW / cm2 was used to simulate the illumination environment; for the IT characteristics of the device, in addition to applying illumination, a bias voltage of 10 V was applied to both ends of the electrode.

[0045] result: Figure 8 The relationship between the current and voltage of the device designed with this film in a dark environment and when the wavelength of light is 254nm. From the figure, it can be seen that the switching efficiency of the device is relatively high. Fig. 9 It shows the relationship between the current and time of the device within five cycles. It can be seen that the photocurrent of the device can reach the milliampere level and has a good photoresponsivity. It can also be seen in the figure that the rise and fall times of the device are relatively fast.

[0046] Brief description of the principle of the present invention: The present invention provides a method for preparing a gallium oxide-based mixed phase film and a method for designing a photodetector based on the film. The method is to grow a monoclinic and hexagonal mixed phase structure film of gallium oxide on one side of the smooth surface of a c-plane single-polished sapphire, and change the crystal growth mode of gallium oxide by adjusting the content of the doped zinc component and the growth temperature and pressure of gallium oxide, so as to achieve the state of coexistence of monoclinic and hexagonal phases in gallium oxide under a high-doping environment with the help of auxiliary ion zinc. At this time, the monoclinic gallium oxide occupies the main position, and the presence of the cubic phase gallium oxide causes the original continuous monoclinic phase grains to break, and the derived grain boundary interface distorts the arrangement of oxygen ions and gallium ions in the monoclinic phase at the atomic scale, a large number of Ga-O bonds are broken and the newly emerged Ga-O bonds in the hexagonal phase are combined, and the doped Zn ions occupy the interstitial and substitutional positions therein, which makes the free electrons and holes blocked by the broken interface, but because the doping process is adopted, the presence of zinc atoms makes up for the oxygen defects and reduces the probability of free carriers being captured by defects. This This will result in a large number of foreign electrons driving the transport of free electrons inside the film under an external electric field due to the potential difference between the two regions. The dark current of the device, which should have increased due to the existence of grain boundaries in a dark state, does not change significantly due to the reduction of defects. When ultraviolet light is applied, the bandgap widths of the two crystal phases are different, which leads to a difference in the number of photogenerated carriers in two adjacent grains under the irradiation of single-wavelength ultraviolet light. This heterojunction-like structure occurs in multiple places inside the film, which increases the light responsiveness of the device on the one hand, and improves the response speed of the device on the other.

[0047] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps described in the disclosure of the present invention can be performed in parallel, sequentially or in different orders, as long as the desired results of the technical solution disclosed in the present invention can be achieved, and this document does not limit this.

[0048] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A gallium oxide mixed phase thin film, characterized in that: The gallium oxide mixed phase film is doped with 5-15 at% zinc, and the crystal phases include two crystal phases: monoclinic β-Ga2O3 and hexagonal ε-Ga2O3.

2. A gallium oxide mixed phase thin film according to claim 1, characterized in that: Prepared by the following method: S1. Clean the substrate and place it in the growth chamber of the MOCVD equipment; heat the substrate tray to 500~950℃ and keep the internal pressure at 1000~2000Pa; S2. Pass high-purity nitrogen for 30 to 50 minutes to exhaust the residual oxygen; set the source temperature of the zinc organic source and gallium organic source precursors, pass the zinc organic source and gallium organic source in equal proportion every 5 to 30 minutes, and maintain for 20 to 50 minutes after reaching the final carrier gas volume of the zinc organic source and gallium organic source; S3. Slowly introduce high-purity oxygen, with the oxygen flow rate increasing from 0 sccm by 50-200 sccm every 10-30 minutes until the oxygen flow rate reaches 500-1000 sccm and then becomes constant, and slowly grow zinc-doped Ga2O3 on the substrate; S4. Grow for 80 to 150 minutes under the oxygen flow state of step S3 to obtain a gallium oxide mixed phase film.

3. A gallium oxide mixed phase thin film according to claim 2, characterized in that: In the step S1, the substrate tray is heated to 750-950°C, and the internal pressure is maintained at 1000Pa.

4. The gallium oxide mixed phase thin film according to claim 2, characterized in that: In the step S2, the source temperatures of the zinc organic source and the gallium organic source precursors are -10~-5°C and 8~12°C respectively; the final carrier gas volumes of the zinc organic source and the gallium organic source are 0.5~1.5sccm and 6~15sccm respectively, the flow rate of the zinc organic source changes from 0sccm to 0.1~0.3sccm, and the flow rate of the gallium organic source changes from 0sccm to 1.5~3.5sccm.

5. The gallium oxide mixed phase thin film according to claim 4, characterized in that: In the step S2, the source temperatures of the zinc organic source and gallium organic source precursors are -8°C and 10°C respectively; the final carrier gas volumes of the zinc organic source and gallium organic source are 1.2 sccm and 7.2 sccm respectively.

6. The gallium oxide mixed phase thin film according to claim 2, characterized in that: In step S3, the oxygen flow rate is increased by 200 sccm every 10 minutes in a linear manner until the oxygen flow rate reaches 800 sccm and then remains constant.

7. A gallium oxide mixed phase thin film according to any one of claims 1 to 6, characterized in that: The thickness of the gallium oxide mixed phase film is 200-400 nm.

8. A gallium oxide mixed phase ultraviolet detector, characterized in that: It comprises, from bottom to top, a substrate, the gallium oxide mixed phase thin film according to claim 1, and interdigital electrodes; The thickness of the interdigital electrode is 50-100 nm, and the effective illumination area is preferably in the range of 0.25-1 mm 2 .

9. The gallium oxide mixed phase ultraviolet detector according to claim 8, characterized in that: The length of the interdigital electrodes is 400-600 um, and the width between the fingers is 10 um; the material of the interdigital electrodes is gold or aluminum.

10. A gallium oxide mixed phase ultraviolet detector according to claim 8 or 9, characterized in that: The method is as follows: epitaxially growing a gallium oxide mixed phase film on a substrate; and depositing the interdigital electrodes on the gallium oxide mixed phase film using a photolithography technique.

Citation Information

Cited By

  • Epsilon-Ga2O3 thin film, metastable-phase gallium oxide ultraviolet detector and preparation method of epsilon-Ga2O3 thin film

    CN120844192A